Transformational Leadership, Technical Competencies And Self-Efficacy On Employee Performance (A Subsidiary Of Dana Pensiun Bank Mandiri Empat-DPBME) - Abdullah, Esfandiari (Jurnal Manajemen, 2018)
The purpose of this study was to determine the effect of transformational leadership, technical competencies and self-efficacy on the employee performance. This study conducted a survey of 70 respondents from the population of 185 employees in PT Wahana Optima Permai (PT WOP, a subsidiary of Bank Mandiri Pension Fund Four-DPBME) Head-Office, and Jakarta, Batam, Surabaya branches. The selected respondents are employees of the business and support units associated with the leasing and management of office buildings. This research used a quantitative survey associative and a path analysis method. The results of this study indicated that transformational leadership, technical competencies, and employee self-efficacy was significantly positive direct influence on employee performance. In order to improve the quality of employee performance, PT WOP should improve the quality of transformational leadership, technical competencies, and self-efficacy employees. As a conclusion, that any change in the quality of transformational leadership, technical competencies, and employee self-efficacy will direct affect employee performance.